Development of English Vocabulary Learning Achievement of Grade 4 Students at Anuban Yasothon School, Yasothon Province During the Covid-19 Outbreak by Using Google Lens with Vocabulary Practice Sets Using Peer Learning Activities: Development of English Vocabulary Learning Achievement of Grade 4 Students at Anuban Yasothon School, Yasothon Province During the Covid-19 Outbreak by Using Google Lens with Vocabulary Practice Sets Using Peer Learning Activities - Polpuak, Rungravee (RATANABUTH JOURNAL, 2024)
This study aimed to 1) compare the students’ English vocabulary learning achievement before and after learning, 2) study the students’ satisfaction with learning by this method, and 3) study the students’ vocabulary retention. The sample group consisted of 117 fourth-grade students selected by purposive sampling. The research instruments were questionnaires and tests. The statistics used in the research were mean, standard deviation, and an experimental design using a single group design before and after the experiment. The results of the study found that 1) the students’ vocabulary learning achievement after learning was higher than before learning in all three academic years, 2) the students had a very high level of satisfaction with the learning methods used in all three years, and 3) the students had vocabulary retention. In summary, the development of English vocabulary learning of fourth-grade students at Anuban Yasothon School, Yasothon Province. During the COVID-19 outbreak by using Google Lens with a set of vocabulary practice with peer-to-peer learning activities showed that the students had higher vocabulary learning achievement after learning than before learning, had the highest level of learning satisfaction, and were able to remember the vocabulary even after 14 days of learning.